Hemn, Goran, Qane, Hardi in Sharif Hussein's Blue Bracelet - Aziz, Saman Jalal (Sulaimani Journal for Humanities, 2019)
This theses deals with: (Shereef Hsen's collection “Blue Necklace”(mlwankey sheen)), especially stylist intertextuality in it, which they depict his cultural and intellectual thoughts and they are nets from a lot of elements. This is direct reason for other texts associations by the mean of arouse previous poems of: (Hemn, Goran, Qanie, Hardi), either directly or indirectly in a new way. He tries to reproducing the former poems in a new artistic functional style. Alot of scholars and critics studied the concept of intertextuality in general or in a specific unit of it, as: Mikhail Bakhtine (dialogisme), Barthe (geology of text), Kristiva, and Gerard Gennete (architexte). In this research the method of intertextuality is applied -specifically stylist intertextuality and gets benefit from stylistc method also. The title of it, is called:”Stylist intertextuality -the poetic style, of: (Hemn, Goran, Qanie, Hardi) in Blue Necklace's collection of Shareef Hsen”.This is done according to concept, and principles of intertextuality. This thesis consists of: introduction, two applied chapters:Chapter one: It specified for Short and brief introduction about stylist phenomenons in poetry which is mentioned by scholars and critics. Chapter two: it is an applicational chapter and entitled:”poetic stylist of Qanie, Hemn, in Blue Necklace's collection”. Chapter three: it is an applicational chapter also, and entitled:”poetic stylist of Hardi and Goran in Blue Necklace's collection”. At the end of the thesis, the most important conclusions resulted from this study are presented, and is followed by the list of references also.